2005
DOI: 10.1007/11604686_31
|View full text |Cite
|
Sign up to set email alerts
|

Approximation Algorithms for Unit Disk Graphs

Abstract: Mobile ad hoc networks are frequently modeled by unit disk graphs. We consider several classical graph theoretic problems on unit disk graphs (Maximum Independent Set, Minimum Vertex Cover, and Minimum (Connected) Dominating Set), which are relevant to such networks.We propose two new notions for unit disk graphs: thickness and density. The thickness of a graph is the number of disk centers in any width 1 slab. If the thickness of a graph is bounded, then the considered problems can be solved in polynomial tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…3). This settles one of the main questions that motivated this paper: recent research [40][41][42] had shown that natural problems having an fptas ω exist, but their position in the hierarchy of approximable problems was hitherto unclear.…”
Section: Introductionmentioning
confidence: 70%
“…3). This settles one of the main questions that motivated this paper: recent research [40][41][42] had shown that natural problems having an fptas ω exist, but their position in the hierarchy of approximable problems was hitherto unclear.…”
Section: Introductionmentioning
confidence: 70%
“…Examples are: planar graphs (of course); graphs of intersections of objects in the plane with bounded objects density (disk graphs with bounded density (see, e.g., [16]) are a special case of these); and graphs with bounded degree and bounded treewidth. The latter can be shown using the tree decompositions implied by the results of Ding and Oporowski [7].…”
Section: Theorem 52 Crossing Parameter 1 Recognition In the Plane Imentioning
confidence: 99%
“…A good survey of many generalizations of these results can be found in [29,31]. Minimum Vertex Cover and Maximum Independent Set in unit-disk graphs and general disk graphs were considered in [37,51,52]. Hochbaum and Maass, and later Chlebík and Chlebíková, considered intersection graphs of d-dimensional boxes in R d [18,35], while Erlebach et al [24] considered intersection graphs of general fat objects in the plane.…”
Section: Related Workmentioning
confidence: 99%